IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA MATERI SEGI EMPAT DALAM PENGAPLIKASIAN KEHIDUPAN SEHARI-HARI - Hartati, Hartati; Marto, Hasia; Mustakim, Mustakim; Insiano, Dewi Angraini (Universitas Tanjungpura, 2025)
The purpose of this research is to determine the implementation of the Independent Learning Curriculum on Quadrilateral Material in Application in Everyday Life. Formulation of the problem in this research How to implement the independent learning curriculum on rectangular material in daily life applications at SDN 10 Tolitoli. This type of research is qualitative research using a descriptive approach where the research uses interview, documentation and observation methods to collect data. Respondents in this research were fourth grade home teachers and 3 students at SDN 10 Tolitoli. The results of research on the implementation of the Independent Learning Curriculum at SDN 10 Tolitoli showed that with an approach based on analyzing student needs, using relevant teaching tools, and integrating values. Pancasila values, learning quadrilateral material becomes more effective and applicable. Even though there has been significant progress, there is a need to continue to adapt and improve methods and support for students to ensure optimal achievement of learning objectives. It can be concluded that the implementation of the Independent Learning Curriculum on Quadrilateral Material in Daily Life Applications at SDN 10 Tolitoli is implemented by teachers have implemented it well.